Women’s Language Features in Emily in Paris: A Sociolinguistics Study - Putri, Meyliana Eka; Beratha, Ni Luh Sutjiati; Maharani, Sang Ayu Isnu (Humanis; Vol 25 No 3 (2021)DO - 10.24843/JH.2021.v25.i03.p02, 2021)
This undergraduate thesis discusses the usage of women’s language features in the television series Emily in Paris. The study analyzes the features of women’s language and its functions in the television series. This study uses observation method in collecting the data. The data were taken from Emily in Paris television series and the movie scripts. Descriptive qualitative method is used to analyze the data by applying women’s language features theory by Lakoff. Based on the analysis and data taken, there are 480 utterance of women’s language features found and ten features of women’s language used by the female characters in Emily in Paris. Lexical hedges or fillers is the most used feature and precise color terms is the least used feature.